Pulling together: A Guide for Indigenization of Post-Secondary Institutions - Sybil Harrison (Author); Janice Simcoe (Author); Dawn SII-YAA-ILTH-SUPT Smith (Author); Jennifer Stein (Author); (Author) (2018)
The "Leaders and Administrators Guide" is part of an open professional learning series developed for staff across post-secondary institutions in British Columbia. Guides in the series include: Foundations; Leaders and Administrators; Curriculum Developers; Teachers and Instructors; Front-line Staff, Student Services, and Advisors; and Researchers. These guides are the result of the Indigenization Project, a collaboration between BCcampus and the Ministry of Advanced Education, Skills and Training. The project was supported by a steering committee of Indigenous education leaders from BC universities, colleges, and institutes, the First Nations Education Steering Committee, the Indigenous Adult and Higher Learning Association, and Métis Nation BC. Also referred to as "Pulling Together: A Guide for Leaders and Administrators"